PENGABDIAN KEPADA MASYARAKAT - Ahmad Safi’e (JOURNAL OF COMMUNITY DEDICATION, 2021)
Community service is an activity that aims to help certain communities in several activities without expecting any form of reward. In general, this program is designed by various universities or institutes in Indonesia to make a real contribution to the Indonesian nation, especially in developing welfare. Community service is one part of the Tri Dharma of Higher Education. Community Service Standards are criteria for the mechanism for implementing Community Service activities. Community Service is an activity of the academic community in the form of utilizing science and technology to advance the welfare of the community and educate the nation's life.